The Role of Musical Frequency Differences in Shaping Listeners’ Brainwave Responses - Djohan Djohan; Indra Kusuma Wardani; Adityo Legowo; Ahmad Insanu Firmansyah; Phakkarawat Sittiprapaporn (Institut Seni Indonesia Yogyakarta, 2025)
Music-based interventions have been widely explored as non-invasive approaches to emotional regulation and anxiety reduction. Within this context, alternative tuning frequencies—particularly 432 Hz and 528 Hz—are frequently used in therapeutic and wellness practices and are often claimed to exert distinct psychophysiological effects. However, empirical evidence supporting differential neural responses to these frequencies remains limited, and existing claims are rarely grounded in direct measurements of brain activity. This study aimed to empirically examine whether music tuned to 432 Hz and 528 Hz produces differential effects on neural oscillatory activity, as measured by brainwave patterns, with particular attention to indicators associated with relaxation and meditative states. A quantitative repeated-measures design was implemented. Ten undergraduate music education students (aged 19–21 years) from the Indonesian Institute of the Arts (ISI) Yogyakarta participated. Each participant listened to the same musical composition presented in two tuning conditions (432 Hz and 528 Hz) in counterbalanced order. Neural activity was recorded using a single-channel EEG device (Neurosky MindWave), which provides spectral estimates of canonical brainwave bands. Delta-band amplitude was selected a priori as the primary outcome measure. Differences between tuning conditions were analyzed using paired-sample t-tests, supplemented by bootstrapping to address the small sample size. Both tuning conditions elicited increased delta-band dominance during music listening. However, no statistically significant difference in delta-band amplitude was observed between the 432 Hz and 528 Hz conditions (t(9) = −1.29, p = 0.229). Bootstrapped confidence intervals corroborated the absence of a reliable frequency-dependent effect. Under controlled within-subject conditions and using single-channel EEG-derived spectral estimates, no evidence was found for differential modulation of delta-band activity between music tuned to 432 Hz and 528 Hz. The results suggest that neural responses are more strongly driven by general musical engagement than by tuning frequency per se. Methodologically, the study highlights both the utility and limitations of low-density EEG for probing music-related neural oscillations and supports the need for future work employing higher spatial resolution EEG, baseline-corrected spectral analyses, and larger samples to test frequency-specific hypotheses with greater sensitivity.